2022
DOI: 10.1021/acsengineeringau.1c00034
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Pressure Drop in Periodic Open Cellular Structures for Intensification of Catalytic Processes

Abstract: Periodic Open Cellular Structures are envisioned as potential enhanced catalyst substrates for heat and mass transferlimited processes. To enable their rational design, in this study, we propose a combined numerical and experimental approach to assess the pressure drop in the tetrakaidekahedral and diamond lattices since generalized correlations are not present in the literature. Deviations are observed between the model predictions available in the literature, which are possibly due to the different methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Averaging the values obtained, it can be said that in all cases there is a deviation in the printed parts that does not exceed 0.6% of the theoretical value of the diameter of the struts according to the CAD. This deviation value is comparable to that obtained by Ferroni et al [40] in their study of POCSs printed with cubic, diamond and Kelvin structures.…”
Section: Struts DIsupporting
confidence: 90%
See 1 more Smart Citation
“…Averaging the values obtained, it can be said that in all cases there is a deviation in the printed parts that does not exceed 0.6% of the theoretical value of the diameter of the struts according to the CAD. This deviation value is comparable to that obtained by Ferroni et al [40] in their study of POCSs printed with cubic, diamond and Kelvin structures.…”
Section: Struts DIsupporting
confidence: 90%
“…Therefore, its analysis can be deepened. In this regard, Ferroni et al [40] proposed the analysis of what they call open windows that allow communication between the different unit cells. In the case of the Kelvin structure, there is a square window corresponding to what we have called the "small detail zone".…”
Section: Struts DImentioning
confidence: 99%
“…These channels could be of any shape, such as circular, square, or triangular cross-section, with the hydraulic diameter scriptO (1) mm and have their walls wash-coated with a catalyst. Low pressure drop, enhanced heat and mass transfer, and ease of scale-up are some characteristics that make monoliths an attractive choice. Since their introduction in the automobile industry for exhaust after-treatment, monoliths are being explored as an alternative multiphase reactor for various chemical processes, such as catalytic oxidation, methanation, and dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its porous structure, multiple streams of fluids can be simultaneously achieved in a single volume, demonstrating excellent potential for the parallelization of multiple fluid channels and high interfacial areas that facilitate mixing/reaction processes 9 . Although efforts have been made to advance the fundamental understanding of the fluid transport processes in the micro-architected materials with lattice structures 4,[10][11][12] , most investigations have focused on single-phase flow. A recent notable work by Dudukovic et al 9 demonstrated the precise manipulation of multi-phase flow in the open lattice structures, where capillary-driven fluid flow along preferential pathways is achieved.…”
Section: Introductionmentioning
confidence: 99%